UMP prepares graduates of management and technical knowledge in business engineering - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) is a well-known, world-class and five-star technology university that offers quality and accredited engineering and technology-based programmes. It is the University of Choice of school leavers and working adults to pursue their studies in diploma, bachelor’s degree, master’s degree and doctorate degree.